Analisis Faktor Psikososial pada Tenaga Kesehatan di KecamatanSungai Raya Kabupaten Kubu Raya - Eli Sutiawati; Gusti Ansahari; Fitri Sukmawati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Introduction: Psychosocial risks can lead to stress and depression in the workplace, causing potential negligence and errors in performing work resulting in workplace accidents. Objective: To analyze the psychosocial risk factors of health workers in health centers that lead to the risk of workplace stress. Methods: Deskriptif analysis research using the Spearman test with a sample 65 people selected by purposive sampling from 186 health workers who served at the Sungai Durian, Sungai Raya Dalam, and Korpri health centers in Kubu Raya Regency. Research variables: Role Confusion, Role Conflict, Quantitative Overload, Qualitative Overload. Career Development, Responsibility for Others and job stress. Data were obtained from the IFRC  and  SDS. Results: Spearman test the most influential is qualitative overload mean value (x̄=11.28) moderate stress (39.24%). severe stress (1.54%), second quantitative overload (x̄=10.25) moderate stress 49.24%, third responsibility to others (x̄=10.26) moderate stress (41.34%). severe stress (3.0).  The significance of the relationship between the variables of psychosocial risk factors and work stress   very strong correlation level, the direction of the relationship is positive and unidirectional between psychosocial risk factors and work stress in health workers. Conclusion: Psychosocial risk factors experienced by health workers quantitative overload and responsibility for others need to be of concern to management there is a decrease in motivation and weakening of activities. Suggestions for management leader and health workers to increasing motivation and managing effective working hours.